The religious dimension of African cosmogonies: a case study of the Igbo of Nigeria - Metuh-Ikenga, Emefie E. (West African Religion, 1978)
This article examines the value of myths as source material of the religious concepts of preliterate peoples. Central to the five Igbo myths studied, stands a creative principle, a High God, lord and preserver of the universe, kind, merciful and good. Evil in the world is not blamed on God, but due to man's misconduct. The findings suggest that there is a vast resource of traditional religious beliefs in African cosmogonies which could help to solve outstanding problems in the studies of African traditional religion especially the problem of the transcendence and immanence of God.
Keywords: Africa; West – Religion; Cosmogony; African; God (African religion); Igbo (African people)